2021
DOI: 10.3748/wjg.v27.i48.8343
|View full text |Cite
|
Sign up to set email alerts
|

Combination of squamous cell carcinoma antigen immunocomplex and alpha-fetoprotein in mid- and long-term prediction of hepatocellular carcinoma among cirrhotic patients

Abstract: BACKGROUND The combination of alpha-fetoprotein (AFP) and squamous cell carcinoma antigen immunocomplex (SCCA-IgM) have been proposed for its use in the screening of hepatocellular carcinoma (HCC). Current screening programs for all cirrhotic patients are controversial and a personalized screening is an unmet need in the precision medicine era. AIM To determine the role of the combination of SCCA-IgM and AFP in predicting mid- and long-term appearance of HCC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Several studies investigated the diagnostic value of SCCA and its immune complex SCCA-IgM in HCC. A recent phase 4 trial with 203 cirrhotic patients revealed that patients with HCC have higher levels of SCCA-IgM than those without it during a five-year follow-up ( 211 ). Another phase 4 trial with 91 patients showed that SCCA-IgM also offers predictive value ( 212 ).…”
Section: Promising New Biomarkers For Clinical Applicationmentioning
confidence: 99%
“…Several studies investigated the diagnostic value of SCCA and its immune complex SCCA-IgM in HCC. A recent phase 4 trial with 203 cirrhotic patients revealed that patients with HCC have higher levels of SCCA-IgM than those without it during a five-year follow-up ( 211 ). Another phase 4 trial with 91 patients showed that SCCA-IgM also offers predictive value ( 212 ).…”
Section: Promising New Biomarkers For Clinical Applicationmentioning
confidence: 99%